Reverse polarity shoulder replacement: Current concepts and review of literature - Lee, Ling Hong (Baishideng Publishing Group Inc, 2014)
Shoulder replacement in cuff tear arthropathy (CTA) is an unsolved challenge. CTA poses a soft tissue deficiency in an arthritic glenohumeral joint which the anatomical total shoulder replacement and hemiarthroplasty cannot reliably provide stability, range of movement, function or satisfactory long term outcome. In the past two decades since the introduction of the reverse shoulder replacement, the prosthesis has evolved and has shown promising results. It is a partially constraint joint by virtue of its design features. The reversal of the concavity and convexity of the joint to the proximal humerus and the glenoid, respectively, also shifts and improves its center of rotation onto the osseous surface of the glenoid with less exposure to shear stress. It is a successful pain relieving procedure, offering good outcome in patients with irreparable massive rotator cuff tear with or without osteoarthritis. Consequently, this has led to wider use and expansion of its indication to include more complex elective and trauma cases. Whereas originally used in the more elderly patients, there is increasingly more demand in the younger patients. It is important to have good quality long term data to support these increasing indications. Therefore, we review the literature on the concepts of reverse shoulder replacement and the contemporary evidence.